Expecting the unexpected: Random tissue barcoding reveals the presence of Pieridae in the diet of ground-dwelling Tenebrionidae (Insecta: Lepidoptera, Coleoptera) - Jurado-Angulo, Pilar; Vasconcelos, Raquel; García-París, Mario (SHILAP Revista de lepidopterología, 2025)
The genus of Tenebrionidae (Coleoptera) Oxycara Solier, 1835 includes 16 species endemic to the Cabo Verde Archipelago. In this study we analysed part of the diet of O. richardi Alluaud, 1936, endemic to the island of Sal, through the non-targeted amplification of a fragment of the mitochondrial gene cytochrome c oxidase subunit I (COI) from a specimen of this species. The results revealed that these detritivorous Coleoptera opportunistically feed on Pontia glauconome (Klug, 1829), a species of Pieridae also present in the archipelago. This finding provides new data on the trophic interactions and feeding behaviour of O. richardi.